Chemical and structural engineering of transition metal boride towards excellent and sustainable hydrogen evolution reaction. (January 2020) - Dutta, Soumen; Han, HyukSu; Je, Minyeong; Choi, Heechae; Kwon, Jiseok; Park, Keemin; Indra, Arindam; Kim, Kang Min; Paik, Ungyu; Song, Taeseup
Abstract: Herein, holey, thin, conductive nickel substituted cobalt molybdenum boride (Ni-CMB) nanosheets have been designed to obtain superior electrochemical HER performance with small overpotential of 69 mV at 10 mA cm -2 current density and lower Tafel slope of 76.3 mV dec -1 in alkaline medium. Incorporation of Ni leads to improved conductivity and favorable hydrogen adsorption on Mo sites, which collectively yield efficient electrocatalytic H2 production from Ni-CMB catalyst. The ultrathin nature (thickness = 5.0 nm) of the designed material expectedly helps to attain high exposure of active sites and facile charge transportation through the nanosheets. Additionally, the decorated mesopores (average size = 3.86 nm) on nanosheets have benefitted towards faster electrolyte diffusion, easy gas escape from catalyst surface to support high electrocatalytic performance. Finally, well-maintained morphology of the sample and evolution of HER active sites in the material have guaranteed long-term, sustainable hydrogen production even at high current densities, which clearly demonstrate its superiority over an expensive electrolyzer (Pt-C) in alkaline water. Graphical abstract: Robust, holey nanosheets of nickel substituted cobalt molybdenum boride exhibits tremendous hydrogen evolution activity and long-term durability by utilizing better electrical conductivity on nickel incorporation and easy charge transportation through the mesoporous channel, respectively. Image 1 Highlights: Nickel-substituted cobalt molybdenum boride (Ni-CMB) nanosheets with controlled chemistry and morphology were successfully synthesized. Strategic nickel incorporation is found to be crucial for the improvement of electrical conductivity and adsorption energy boosting electrocatalytic activity. Robust nature of the material and sustainable production of hydrogen for long time scale is achieved via structural engineering of Ni-CMB. DFT calculations revealed individual roles of elements in Ni-CMB for HER, which can help to understand catalytic reaction mechanism.